Clinical and Cost-effectiveness of a Comprehensive geriatric assessment and management for Canadian elders with Cancer—the 5C study: a study protocol for a randomised controlled phase III trial. Issue 5 (10th May 2019) - Puts, Martine T E; Hsu, Tina; Mariano, Caroline; Monette, Johanne; Brennenstuhl, Sarah; Pitters, Eric; Ray, Jack; Wan-Chow-Wah, Doreen; Kozlowski, Natascha; Krzyzanowska, Monika; Amir, Eitan; Elser, Christine; et al.
Abstract : Introduction: Geriatric assessment and management is recommended for older adults with cancer referred for chemotherapy but no randomised controlled trial has been completed of this intervention in the oncology setting. Trial design: A two-group parallel single blind multi-centre randomised trial with a companion trial-based economic evaluation from both payer and societal perspectives with process evaluation. Participants: A total of 350 participants aged 70+, diagnosed with a solid tumour, lymphoma or myeloma, referred for first/second line chemotherapy, who speak English/French, have an Eastern Collaborative Oncology Group Performance Status 0–2 will be recruited. All participants will be followed for 12 months. Intervention: Geriatric assessment and management for 6 months. The control group will receive usual oncologic care. All participants will receive a monthly healthy ageing booklet for 6 months. Objective: To study the clinical and cost-effectiveness of geriatric assessment and management in optimising outcomes compared with usual oncology care. Randomisation: Participants will be allocated to one of the two arms in a 1:1 ratio. The randomisation will be stratified by centre and treatment intent (palliative vs other). Outcome: Quality of life. Secondary outcomes: (1) Cost-effectiveness, (2) functional status, (3) number of geriatric issues successfully addressed, (4) grades3–5 treatment toxicity, (5) healthcare use, (6) satisfaction, (7) cancer treatment plan modification and (8) overall survival. Planned analysis: For the primary outcome we will use a pattern mixture model using an intent-to-treat approach (at 3, 6 and12 months). We will conduct a cost-utility analysis alongside this clinical trial. For secondary outcomes 2–4, we will use a variety of methods. Ethics and dissemination: Our study has been approved by all required REBs. We will disseminate our findings to stakeholders locally, nationally and internationally and by publishing the findings. Trial registration number: NCT03154671 .